A REVIEW ON ABERNATHY MALFORMATION - Kumar, Deepak; Shrivastava, Saumya; Singh, M. P. Khinchi Surya Pratap; Khan, Mohd. Shahid (Asian Journal of Pharmaceutical Research and Development, 2017)
The first account of an absent portal vein and a congenital mesenteric-caval shunt was given by John Abernethy in 1793. Five new cases of congenital extra hepatic Porto caval shunts are described in this report .One end-to-side shunt with congenital absence of the portal vein (type 1 shunt). Four are side-to-side (type 2) shunts of which there have been only two previous reports. Type 1 shunts are associated with other congenital abnormalities and have only been recognized in girls. Five of these cases developed liver tumors. Type 2 shunts are rarer, and four of five have been boys. They are not usually associated with other anomalies. Encephalopathy may be associated with these shunts in adults, and surgical closure of the side-to-side shunts is therefore recommended. End-to-side shunts are not correctable but the abnormal anatomy may create a problem for hepatic transplantation, should this be necessary for associated disorders such as biliary atresia. ―The Abernethy Malformation‖ would seem to be a suitable eponym for congenital extra hepatic Porto caval shunts.